A study of the Factors affecting Seepage and Methods for Evaluating Losses due to Seepage in Small irrigation Channels. - Gorreia, J F (Journal of Soil and Water Conservation, 2022)
Seepage has beefi defined as the movement of water into or out of the ground. Acc or ding to ('seepage is the perco- Meinzer, (l) lation through the surface of the lithosphere or through the walls of large opening in it, such as caves or artificial excavations". Perco- lation occurs through smal}er in- terstices and it may be considered as a slower movement of water.Losses of water due to seepage occur in irrigation channels which are not lined with the proper type It plays a very of lining material. important part in arid regions where irrigation water flowing in channels forms the chief source of water supply to crops. The problem is serious in highly permeable earth channels, where the only solution is the lining of the channel with the proper type of lining material. The amount of seepage may be measured in cubic feet per square foot of water surface per 24 hours; in cubic feet per second per mile; or in percentage of total flow per mile. In this paper seepage will mean movement of water into or irrigation channels out of the through the interstices in the bed material.